A Comparative Study of Endoderm Differentiation Between Activin A and Small Molecules - Li, Qiang; Li, Jin; Wang, Ping; He, Xiaoqun; Hong, Mingzhao; Liu, Feng (Experimental and Clinical Endocrinology & Diabetes, 2023)
Small molecules such as ROCK inhibitors (Fasudil) and inducer of definitive endoderm 1 (IDE1) can promote differentiation of definitive endoderm, but their effects remain controversial. Therefore, we attempted to verify the effect of these small molecules on promoting definitive endoderm differentiation and found that Fasudil or IDE1 alone could not achieve a similar effect as activin A. On the contrary, CHIR99021 could efficiently promote definitive endoderm differentiation. Nearly 43.4% of experimental cells were SRY-box transcription factor 17 (SOX17)-positive under the synergistic effect of IDE1 and CHIR99021, but its ability to differentiate towards definitive endoderm was still insufficient. Transcriptional analysis and comparison of IDE1 and CHIR99021 synergistic groups (IC) and activin A and CHIR99021 synergistic groups (AC) showed significantly down-regulated definitive endoderm markers in the IC group compared with those in the AC group and the differences between the two groups were mainly due to bone morphogenetic proteins (BMP4) and fibroblast growth factor 17 (FGF17). Further single-cell transcriptome analysis revealed lower expression of BMP4 in SOX17-positive populations, while mothers against decapentaplegic homolog (SMAD) protein translation signal and FGF17 in the AC group were higher than that in the IC group. Western blot analysis showed a significant difference in levels of p-SMAD2/3 between AC and IC groups, which suggests that regulating p-SMAD2/3 may provide a reference to improve the differentiation of definitive endoderm.
Keywords: Definitive endoderm; activin A; IDE1; CHIR99021